Influence of Perceived Adoption of Tokenized Derivatives on Market Liquidity, Pricing Efficiency - Handini, Sri; Garry Brumadyadisty; Soekiman, Susanto; Krisprimandoyo, Denpharanto Agung (Institut Bisnis dan Informatika Kesatuan, 2025)
The emergence of tokenized derivatives marks a significant innovation in decentralized finance (DeFi), offering potential improvements in market liquidity and pricing efficiency through blockchain-enabled mechanisms. As financial markets evolve with the integration of smart contracts and distributed ledgers, understanding how user perceptions influence market dynamics becomes increasingly critical. This study aims to examine the effect of perceived adoption of tokenized derivatives on market liquidity and pricing efficiency, while assessing the mediating role of liquidity in this relationship. Grounded in the Technology Acceptance Model (TAM), Innovation Diffusion Theory (IDT), and Market Microstructure Theory (MMT), the research utilizes Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data from 150 fintech professionals based in Surabaya. The analysis reveals that perceived adoption significantly enhances both liquidity and pricing efficiency, with liquidity serving as a key mediating variable. These findings underscore the importance of behavioral constructs in shaping decentralized market outcomes and provide strategic insights for regulators, fintech developers, and policymakers aiming to accelerate adoption and improve market functionality in the DeFi landscape through perception-driven approaches.